ANALYSIS OF THE CONCEPT OF IDENTITY IN THE CONTEXT OF CULTURAL HERITAGE INTERPRETATION - Pilyak , Sergey (Научно-просветительский журнал "Наставник", 2021)
Identification and translation of regional identity is one of the most important stages in the socio-economic development of regions, the formation of an attractive image of the territory. In addition, depending on the unifying features, it is possible to distinguish professional, age, gender, and other types of identity. Identity as a certain community, united by some common properties or features, can arise both in the interpreter and in relation to the object of interpretation. Taking into account the above, the author proposes to consider the principle of identity as a component of the specifics of the interpretation of cultural heritage.